PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DIDI KALIBRASI INDONESIA DI JAKARTA SELATAN - Fatimah Al Zahro; Abu Bakar Dja’far (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of Work Discipline and Job Satisfaction on employee performance at PT. Didi Kalibrasi Indonesia in South Jakarta, both partially and simultaneously. The type of research is associative with a quantitative approach. The research sample consisted of 57 respondents. The data analysis methods used in this study include instrument tests consisting of validity tests, reliability tests, and classical assumption tests, which consist of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, correlation coefficient, coefficient of determination test, and hypothesis testing consisting of partial t-tests and simultaneous F-tests. The results showed that Work Discipline had an effect on employee performance with a t-value greater than the t-table (8.083 > 1.674) and a significance value of 0.000 < 0.05. Job Satisfaction had a positive and significant effect on employee performance with a t-value greater than the t-table (7.397 > 1.674) and a significance value of 0.000 < 0.05. Work Discipline and Job Satisfaction together had a positive and significant effect on employee performance with an F-value greater than the F-table (43.565 > 3.168) and a significance value of 0.000 < 0.05. The R-square value indicates that Work Discipline and Job Satisfaction jointly contribute an influence on employee performance of 61.7%, while the remaining 38.3% is influenced by other factors or variables not examined in this study. Keywords: Work Discipline, Job Satisfaction, Employee Performance